Is It a Good Time to Be a Pharmacist in the US? - Surrey M. Walton; Henri R. Manasse (MDPI AG, 2018)
The labor market for pharmacists in the United States has seen significant dynamics over the past couple of decades in both demand and supply. The purpose of this brief editorial is to discuss some key concerns for pharmacists in the current labor market and over the next decade. A key issue in evaluating how pharmacists will fare in moving forward into expanded clinical roles and functions will be the degree to which they expand their professional autonomy.